Comparative Characterization of Carica papaya Fibers Extracted by Retting and Alkaline Treatment for Biocomposites - Roland Yves Olembe; Armel Edwige Mewoli; Abel Emmanuel Njom; Victor Jos Evina Eyamo; Marie Josette Ndengue; Florent Biyeme; Georges Armand Beguel Ndjock; Mélek Ayadi; César Segovia; Emmanuel Christian Essama; Paulette Roseline Kenfack Momo; Betene Ebanda Fabien; et al. (Advances in Polymer Technology)
This study investigates the effects of different extraction methods—water retting and alkali treatments using 5% and 10% NaOH—on the properties of Carica papaya fibers (CPFs) for sustainable composite applications. Physical, chemical, thermal, and mechanical properties of the fibers were analyzed using Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and tensile testing. Results showed that alkaline treatment enhanced fiber purity, crystallinity, and thermal stability, with 5% NaOH offering the best compromise between strength and flexibility. Crystallinity index (CI) reached 64.06%, and tensile strength improved significantly (276.98 MPa for CPF5 compared to 116.88 MPa for untreated fibers). Thermal degradation onset increased by 13.5°C compared to retted fibers. Analysis of variance (ANOVA) and Tukey HSD tests confirmed statistically significant improvements. Although no composites were fabricated, the thermal and mechanical properties of treated CPF suggest compatibility with thermoplastic matrices such as polypropylene and PLA. These findings demonstrate that Carica papaya (CP) pseudostem, an agricultural residue, can be a promising reinforcement source for biodegradable composites. Further investigation is needed to optimize fiber–matrix interactions and long-term durability under environmental stress.